Synthesis of quinoxaline derivatives and their antibacterial activity against pathogenic bacteria - Khatoon, Hena (2023)
Quinoxaline derivatives, in which nitrogen substitutes for one or more carbon atoms in the naphthalene ring, are a significant class of hetero-cyclic compounds, and are well known in the pharmaceutical industry, and have been shown to possess a broad spectrum of biological activities. These formulations make use of straightforward techniques to create quinoxaline derivatives from aryl-thiols (mercaptan) compounds. Inspired by the biological prominence of quinoxaline derivatives and trying to solve bacterial resistance problems, in this study, 24 quinoxaline derivatives were synthesized. These series were synthesized from the reaction of 2,3-dichloroquinoxaline (2,3-DCQ), 2- chloroquinoxaline (2-CQ), 2-chloro-3-methyl quinoxaline (3-MCQ) with two different aromatic aryl-thiols (mercaptan) and phenols in a single step to investigate the activities aromatic derivatives. The compounds were synthesized using different solvent systems, dimethylformamide (DMF)/ potassium triphosphate (K3PO4), methanol (MeOH)/ triethylamine (Et3N), acetone/ 0.1N sodium hydroxide (NaOH), and dimethylformamide/potassium carbonate (DMF/ K2CO3), depending on the nucleophilicity of the mercaptan compounds. A comparative study was used to compare the efficiency of these solvent systems to synthesize the same target compounds regarding the reaction time, percentage yield, purity of the compounds, and benignity towards the environment. The structures of twenty-four compounds were confirmed by applying spectroscopic analysis (1D and 2D nuclear magnetic resonance (NMR), Fourier transform infrared (FTIR), and gas chromatography mass spectrometry (GCMS)). In addition, four different bacteria were used to evaluate the antibacterial efficacy of the compounds (1-15): three Gram-negative (Escherichia coli (E. coli), Salmonella Typhimurium, Enterobacter aerogenes), and Gram-positive (Bacillus Pumilus). To assess a drug's efficacy against a particular bacterial species, the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) assays are frequently performed. The synthesized molecules displayed a better role as antibacterial agents than their analogs. Compounds 8 and 14 have the strongest antibacterial activity for Bacillus pumilus, with an inhibition zone of 10 and 9 mm (MIC ranging at about 5 and 2.5 mg/mL, followed by MBC at 2.5 mg/mL). A similar pattern of antibacterial properties was observed against E. coli. Compounds 1 and 3 have an inhibition zone (IZ) of 7 and 6 mm and MIC of 1.25 and 5 mg/mL, respectively. Similarly, di-substituted derivatives 8, 13, and 14 have the best IZ of 11, 12, and 12 (mm) (MIC of 2.5, 5 and 5 mg/mL, followed by MBC of 2.5, 5 and 2.5 mg/mL). Due to impressive antibacterial properties, the compounds were also studied for their physio-chemical and drug-likeness properties via Swiss ADME software. It was found that molecules 9 and 11 displayed remarkable drug-likeness properties without violating the rules and a bio-availability score of 0.55. Like-wise molecular docking studies provided good interactions between protein and ligands (synthesized compounds). The molecular docking studies were performed on compounds 8, 12, 13, 14, 19 and 21. Compound 12 had the best docking score of -8.60 kcal/mol followed by compound 13 (-8.01 kcal/mol) for DNA gyrase protein. Compounds 12 and 13 are classified as di-substituted quinoxaline derivatives having electron-withdrawing -NO2 and -COOH, which enhanced the formation of Hbonding with amino acids. Compounds 12, 13 and 8 had a similar effect with PBP1a protein (-8.01 kcal/mol for compound 8, -8.16 kcal/mol for compound 12 and -7.97 kcal/mol for compound 13). The reaction conditions for the synthesized compounds were straightforward and produced using SNAr (aromatic nucleophilic substitution reaction) mechanism. Antibacterial assays and docking investigations revealed that the sulfur bridge made the molecule into a powerful antibacterial agent. Two symmetrical sulfur bridges were shown to have increased antibacterial activity, making them a prime option for medication development.